The Dosage of Superplasticizer in Cemented Coal Waste Backfill Material Based on Response Surface Methodology. (20th January 2019) - Li, Qingdong; Feng, Guorui; Guo, Yuxia; Qi, Tingye; Du, Xianjie; Wang, Zehua; Li, Huayun
Abstract : Cemented coal waste backfill material (CCWBM) is developed for backfilling the goaf in coal mines. As fresh CCWBM slurry is generally transported into underground openings through a pipeline, the fluidity of fresh slurry becomes one of the most important properties. Adding superplasticizer is considered to improve the flow performance of the slurry without alerting the mechanical performance of filling body. The dosage of superplasticizer (SP) is related to filling cost, thus response surface methodology (RSM) is adopted to study the influence of material composition on SP when target slump is 250 mm. The effects of fly ash content, fine gangue ratio, and mass concentration on SP are analyzed using the software of Design-Expert and central composite design (CCD), and models are established for SP. Results show that the SP model coincides greatly with the test results and can be applied to analyze and predict SP in CCWBM. Mass concentration, fly ash content, and fine gangue ratio influence SP from high to low. The interaction of fine gangue ratio and mass concentration between SP is the most significant. The fact that the improved aggregate space model can be applied to analyze the fluidity of CCWBM is proved too. The research results provide guidance for the design and preparation of CCWBM with favourable performance and low cost in practical production.